Age- and sex- related patterns in hematobiochemical and anthropometric parameters of Macaca monkeys - Hyeon-Mu Cho; Se-Hee Choe; Hye-Ri Park; Ja-Rang Lee; Min-Gyeong Ko; Yun-Jung Lee; Kang Jin Jeong; Bon Sang Koo; Kyung Seob Lim; Gyu-Seo Bae; Eun Su Jeon; Philyong Kang; et al. (GeroScience, 2026)

Food safety implications of microbial communities in enoki mushrooms: Impact of farm environments and distribution channels - Ga-Hee Ban; Bo-Kyeong Kim; Min Suk Rhee; Se-Ri Kim; Sun Ae Kim (Food Control, 2026)

Genome-wide association study of upper thermal tolerance in Atlantic salmon (Salmo salar) - Min Sung Kim; Jae Yong Han; Ji Been Park; Ju Yeong Kang; Ju Ri Kwak; Sung Oh Park; Se Hwan Kim; Woo-Jai Lee (Aquaculture, 2026)

Tribuli Fructus alleviates 1-methyl-4-phenyl 1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson’s disease by suppressing neuroinflammation via JNK signaling - Jin Hee Kim; Eugene Huh; Hyeyoon Eo; Jin Se Kim; Youngji Kwon; In Gyoung Ju; Yujin Choi; Hae-Jee Yoon; So-Ri Son; Dae Sik Jang; Seon-Pyo Hong; Hi-Joon Park; et al. (Metabolic Brain Disease, 2024)

Inulae Flos has Anti-Depressive Effects by Suppressing Neuroinflammation and Recovering Dysfunction of HPA-axis - Jin Se Kim; Jin Hee Kim; Hyeyoon Eo; In Gyoung Ju; So-ri Son; Ji-Woon Kim; Dae Sik Jang; Myung Sook Oh (Molecular Neurobiology, 2024)

Selective synthesis of soft and hard carbons from a single precursor through tailor-made stabilization for anode in sodium-ion batteries - Gwanwon Lee; Kyoung Bin Min; Min Eui Lee; Youn-Ki Lee; Hae Ri Lee; Sung-Soo Kim; Se Youn Cho; Han-Ik Joh; Young-Kwan Kim; Sungho Lee (Chemical Engineering Journal, 2024)

Microbial succession during button mushroom (Agaricus bisporus) production evaluated via high-throughput sequencing - Ga-Hee Ban; Jin-Hee Kim; Sun Ae Kim; Min Suk Rhee; Song Yi Choi; In Jun Hwang; Se-Ri Kim (Food Microbiology, 2023)

Efficacy of combined caprylic acid and thymol treatments for inactivation of Listeria monocytogenes on enoki mushrooms in household and food-service establishments - Seo Young Chung; Tae Jin Cho; Hary Yu; Seon Gyeong Park; Se-Ri Kim; Sun Ae Kim; Min Suk Rhee (Food Research International, 2023)

Preliminary investigation of Late Pleistocene fauna from Ryonggok Cave No. 1, Sangwon County, North Hwanghae Province, Democratic People's Republic of Korea - Rye Sun Choe; Kum Sik Han; Se Chan Kim; Myong Hyok Ri; Jae Nam Ri (Journal of Quaternary Science, 2021)
The investigation of a limestone cave on the Ryonggok‐ri of Sangwon County, North Hwanghae Province, DPRK, has yielded many faunal remains including Late Pleistocene deer, brown bears and horses. Uranium series dating of fossil teeth yielded dates of ~72ka at the base of Layer 2 – the bone‐bearing unit – and ~44ka at the top. The rich and diverse mammal remains of Ryonggok Cave No. 1 are indicative of warm and humid temperate conditions during the Late Pleistocene, and reflect the presence of both dense forests and open grassland. In addition, pollen and spores from the site include two families and 24 genera of trees, six families and a genus of grasses and herbs, and two families and six genera of ferns, corroborating the environments inferred from the faunal remains.

A Novel Compound ITC-3 Activates the Nrf2 Signaling and Provides Neuroprotection in Parkinson’s Disease Models - Ji Ae Lee; Hyo Jin Son; Ki Duk Park; Se Hee Han; Nari Shin; Ji Hyun Kim; Hye Ri Kim; Dong Jin Kim; Onyou Hwang (Neurotoxicity Research, 2015)